Nursing care plans for patients with ventricular assist devices: A holistic evaluation based on clinical observations and practice recommendations: Ventricular assist device nursing - Bektaş, Neslihan (Journal of Surgery and Medicine, 2026)
Ventricular assist device (VAD) nursing is a critical specialty in the management of patients with advanced heart failure and cardiomyopathy. VAD nurses play an essential role in the preoperative preparation, intraoperative coordination, and postoperative care of patients receiving mechanical circulatory support, particularly those awaiting heart transplantation. These devices assist in improving cardiac function, but their use carries risks, such as infection, bleeding, thrombosis, device malfunction, and psychological challenges. Therefore, VAD nurses must possess expertise not only in general nursing care but also in infection prevention, anticoagulation management, patient education, and psychosocial support. As integral members of multidisciplinary teams, VAD nurses are responsible for educating patients on device management, ensuring safety, and promoting quality of life. With technological advancements, the role of VAD nurses has become increasingly significant in preventing complications and maintaining patient stability. In conclusion, VAD nursing is vital for improving patient outcomes and enhancing quality of life. Continued education and interprofessional collaboration are essential for advancing expertise and ensuring high-quality patient care.